Escaping Titanic : a young girl's true story of survival - Lorbiecki, Marybeth (Picture Window Books, 2012)
Presents the story of 12-year-old Elizabeth Becker, who was returning from India to America with her mother and siblings on the Titanic when the great ship collided with an iceberg.